INTEGRITY AND HISBAH IN THE ZAKAT MANAGEMENT MECHANISM ON ZAKAT INSTITUTIONS - Caturida Meiwanto Doktoralina; Zakaria Bahari (Journal of Islamic, Social, Economics and Development, 2019)
Integrity and accountable monitoring activities (Hisbah) in zakat management require quality acceleration of mechanisms. The requirements are that the zakat institution should make contributions to the implementation of zakat management by displaying real data of the muzakki and mustahik at each zakat institution. The purpose of this study is to provide a role of integrity and dedication in the institution's zakat management mechanism, in particular on the collection and distribution of zakat in Indonesia. There are two research objectives: first, how the mechanism of integrity and hisbah is done for the charity payment activities at the charity institution, and second, the role of integrity and hisbah has been done by dividing the citation nisab by giving alms — a methodology using documentation related to integrity and hisbah in the mechanism of collection and distribution of zakat. The data is derived from the National Zakat Agency Report (BAZNAS) and empirical research documents. The content analysis of this document shows that the zakat institution requires integrity and worship. This is the basis for affirming professional attitudes in building trust in institutions. In addition, integrity and charity can also be the basic standard for zakat institutions for the collection and distribution of zakat. The implications of this study will help raise awareness of the importance of integrity and spirituality in the collection and distribution of zakat in zakat institutions. This study provides an overview of the factors that are essential to the charity's institution in enhancing the integrity and impact of zakat management, especially in matters of collection and distribution of zakat. This study explores the concept of data integrity from an Islamic perspective. The hope is that zakat collection and distribution in Indonesia can contribute to resolving the lack of zakat collection.